Variations of workload and well-being measures across a professional basketball season - Ferreira, M.; Camões, M.; Franco Lima, R.; Silva, R.; de Oliveira Castro, H.; Mendes, M.; Bezerra, P.; Clemente, F. M. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2021)
The aims of this study were: (i) to describe weekly variations of acute load (AL), acute:chronic workload ratio, delayed onset muscle soreness (DOMS), and fatigue; (ii) to analyze variations of weekly workload and well-being in three periods of the season (P1, P2, and P3); and (iii) to analyze the relationships between workload and well-being measures. Fifteen professional basketball players from a first-league European club were monitored throughout the season using the CR-10 Borg scale and the Hooper questionnaire. Weekly AL and acute:chronic workload ratio (ACWR) were weekly calculated for monitoring of the internal load. In addition, DOMS and fatigue values were weekly calculated. Greater AL, DOMS, and fatigue values were found during the early season, and the highest ACWR value was found during the second period. Overall, AL presented large correlations with DOMS (r=0.60) and fatigue (r=0.62). The results of this study indicate that load is higher in the first period and then decreases throughout the season. The results also showed that AL is more closely related to well-being parameters than ACWR.